On Anonymity and Indifference - bartilet, jeffrey (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
The paper articulates, in broad strokes, an idea of responsibility that is affixed to a general attitude of availability and service. That to respond to, that to be responsive is to breakthrough the barriers of complacency, it is to be open to the unsettling appeal for justice amidst injustice, and that to exist is not to be only for oneself.